THE (DES)CONSTRUCTION OF THE CONCEPT OF ADHD AND MEDICALIZATION OF EDUCATION IN THE LIGHT OF HISTORICAL-CULTURAL PSYCHOLOGY - Cristovam Moreira de Santana, José; Maria Carvalho da Graça Furtado, Izaura (Revista Gênero e Interdisciplinaridade, 2023)
This article aims to present a critical analysis of the concepts that encompass ADHD. In this sense, it is understood that contrary to some of the opinions described, the influence of the family environment and the entire social, historical and cultural context of the individual determines the incidence or not of “distant” factors of the so-called standard behavior and, already stigmatizes the individual, sometimes from early childhood, to the label of having a disorder.